Activation of the phenylpropanoid biosynthesis pathway reveals a novel action mechanism of the elicitor effect of chitosan on avocado fruit epicarp. (July 2019) - Xoca-Orozco, Luis-Ángel; Aguilera-Aguirre, Selene; Vega-Arreguín, Julio; Acevedo-Hernández, Gustavo; Tovar-Pérez, Erik; Stoll, Alexandra; Herrera-Estrella, Luis; Chacón-López, Alejandra
Abstract: Secondary metabolites play an important role in the avocado fruit defense system. Phenolic compounds are the main biosynthesized metabolites of this system response. Our objective in this investigation was to evaluate the induction of specific metabolic pathways using chitosan as an elicitor. Extracts obtained from avocado in intermediate and consumption maturity stages treated with chitosan exhibited an increase in antifungal activity, which caused inhibition of mycelial growth and a decrease in sporulation as well as spore germination of Colletotrichum gloeosporioides . Additionally, RNA from epicarp of the fruits treated and untreated with chitosan was obtained in order to evaluate the expression of genes related to phenylpropanoids and the antifungal compound 1-acetoxy-2-hydroxy-4-oxo-heneicosa-12, 15-diene biosynthesis. An increased in gene expression of genes that participates in the phenylpropanoids route was observed during the stage of physiological fruit maturity, others genes such as Flavonol synthase (Fls), increased only in samples obtained from fruit treated with chitosan at consumption maturity. Our results reveal a new molecular mechanism where chitosan induces a specific accumulation of phenylpropanoids and antifungal diene; this partially explains avocado's resistance against fungal pathogens. Finally, we discuss the molecular connections between chitosan induction and gene expression to explain the biological events that orchestrate the resistance pathways in fruits. Graphical abstract: Unlabelled Image Highlights: Extract of fruits treated with chitosan showed a greater in vitro inhibition of C. gloesporoiodes. Genes expression suggests that phenylpropanoid route is stimulated under chitosan treatment. The expression of genes involved in the biosynthesis of persin increased considerably in chitosan treatments. The avocado fruits treated with chitosan acquire resistance to fungal by the presence of persin with antifungal effect.